Genesis and development of a scientific fact - Fleck, Ludwik (Chicago The University of Chicago Press, 1979)
Originally published in German in 1935, this monograph anticipated solutions to problems of scientific progress, the truth of scientific fact and the role of error in science now associated with the work of Thomas Kuhn and others. Arguing that every scientific concept and theoryincluding his ownis culturally conditioned, Fleck was appreciably ahead of his time. And as Kuhn observes in his foreword, "Though much has occurred since its publication, it remains a brilliant and largely unexploited resource.""To many scientists just as to many historians and philosophers of science facts are things that simply are the case: they are discovered through properly passive observation of natural reality. To such views Fleck replies that facts are invented, not discovered. Moreover, the appearance of scientific facts as discovered things is itself a social construction, a made thing. A work of transparent brilliance, one of the most significant contributions toward a thoroughly sociological account of scientific knowledge."Steven Shapin, Science